1978
DOI: 10.1002/art.1780210106
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous C2 deficiency with fulminant lupus erythematosus. severe nephritis via the alternative complement pathway

Abstract: Absence of C2 was identified in an 18-year-old white male with progressive and rapidly fatal lupus nephritis. Genetic studies of the patient and 8 family members linked this deficiency with the HLA haplotype A10/B18, for which the patient was homozygous. High titers (1 : 1600) of anti-RNP antibodies, as well as antibodies to double-stranded DNA, were present. Serum levels of properdin factor B were persistently decreased, whereas levels of Clq and C3 intermittently were low. Biopsies of skin and kidney showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
1

Year Published

1978
1978
1989
1989

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 40 publications
0
6
1
Order By: Relevance
“…In one patient with severe extra renal SLE, known to have a homozygous C2 deficiency, C1 activation was found during active disease, but no evidence of alternative pathway activation, which was in contrast to previous findings in a C2-deficient patient with renal involvement (10).…”
Section: Discussioncontrasting
confidence: 54%
“…In one patient with severe extra renal SLE, known to have a homozygous C2 deficiency, C1 activation was found during active disease, but no evidence of alternative pathway activation, which was in contrast to previous findings in a C2-deficient patient with renal involvement (10).…”
Section: Discussioncontrasting
confidence: 54%
“…This experience emphasizes the usefulness of assays in gel for detection of patients with deficiency of C7. We anticipate that such semiquantitative screening assays, because of their ease of performance, general accessability, and demonstration of unusual morphologic features such as those described above, will serve as usefuil adjuncts to the (juantitative hemolytic tube and protein assays, and will help to uncover patients with abnormalities of the complement system generally (20,34).…”
Section: Discussionmentioning
confidence: 99%
“…In our hands, both modifications of the deficiency, Friend et al [8] in 1975 pre sented a family that allows the assumption of a C2 deficiency locus outside HLA-D. All the other recombinants so far published in families with C2 deficiency are compati ble with this localization: Gewürz et al [11] have shown an HLA-A/B crossover where the C2° gene segregated with the HLA-B fragment. In two heterozygous C2-deficient families with HLA-B/D crossovers in the material of Raum et al [25], C2° follows the HLA-D part.…”
Section: Discussionmentioning
confidence: 62%